Presenilin1 familial Alzheimer disease mutants inactivate EFNB1- and BDNF-dependent neuroprotection against excitotoxicity by affecting neuroprotective complexes of N-methyl-d-aspartate receptor. Issue 2 (20th July 2020) - Al Rahim, Md; Yoon, Yonejung; Dimovasili, Christina; Shao, Zhiping; Huang, Qian; Zhang, Emily; Kezunovic, Nebojsa; Chen, Lei; Schaffner, Adam; Huntley, George W; Ubarretxena-Belandia, Iban; Georgakopoulos, Anastasios; et al.
Abstract: Excitotoxicity is thought to play key roles in brain neurodegeneration and stroke. Here we show that neuroprotection against excitotoxicity by trophic factors EFNB1 and brain-derived neurotrophic factor (called here factors) requires de novo formation of 'survival complexes' which are factor-stimulated complexes of N -methyl-d -aspartate receptor with factor receptor and presenilin 1. Absence of presenilin 1 reduces the formation of survival complexes and abolishes neuroprotection. EPH receptor B2- and N -methyl-d -aspartate receptor-derived peptides designed to disrupt formation of survival complexes also decrease the factor-stimulated neuroprotection. Strikingly, factor-dependent neuroprotection and levels of the de novo factor-stimulated survival complexes decrease dramatically in neurons expressing presenilin 1 familial Alzheimer disease mutants. Mouse neurons and brains expressing presenilin 1 familial Alzheimer disease mutants contain increased amounts of constitutive presenilin 1– N -methyl-d -aspartate receptor complexes unresponsive to factors. Interestingly, the stability of the familial Alzheimer disease presenilin 1– N -methyl-d -aspartate receptor complexes differs from that of wild type complexes and neurons of mutant-expressing brains are more vulnerable to cerebral ischaemia than neurons of wild type brains. Furthermore, N -methyl-d -aspartate receptor-mediated excitatory post-synaptic currents at CA1 synapses are altered by presenilin 1 familial Alzheimer disease mutants. Importantly, high levels of presenilin 1– N -methyl-d -aspartate receptor complexes are also found in post-mortem brains of Alzheimer disease patients expressing presenilin 1 familial Alzheimer disease mutants. Together, our data identify a novel presenilin 1-dependent neuroprotective mechanism against excitotoxicity and indicate a pathway by which presenilin 1 familial Alzheimer disease mutants decrease factor-depended neuroprotection against excitotoxicity and ischaemia in the absence of Alzheimer disease neuropathological hallmarks which may form downstream of neuronal damage. These findings have implications for the pathogenic effects of familial Alzheimer disease mutants and therapeutic strategies. Abstract : We describe a presenilin 1-dependent mechanism by which neurotrophic factors protect neurons rom excitotoxicity, a condition with crucial roles in neurodegeneration and stroke. The mechanism includes presenilin1-dependent N -methyl-d -aspartate receptor complexes with factor receptors. Familial Alzheimer disease mutants alter N -methyl-d -aspartate receptor-presenilin1 associations and block factor-dependent neuroprotection in absence of Alzheimer disease hallmarks. Graphical Abstract: